2015 12th International Conference on the European Energy Market (EEM) 2015
DOI: 10.1109/eem.2015.7216712
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of demand side flexibility in a smart grid: A review for European market design

Abstract: International audienceThe increased share of renewable generation and the integration of Distributed Generation (DG) require more electricity system flexibility. One way to increase this flexibility is to use the potentials of demand response (DR). In order to activate the full range of customers in DR, a new market intermediary actor is needed to aggregate the resources in an adequate technical and economical format. These actors, so called " aggregators " , can act as flexibility providers to support securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 7 publications
1
21
0
1
Order By: Relevance
“…To ensure fair compensation for participation of intelligent building energy systems in the service markets, it is of critical importance to accurately forecast energy consumption baseline associated with nominal operation. This is consistent with current paradigms for grid operation and market designs, as well as proposed market designs for aggregated demand side flexibility as presented in [6]. In [7] the authors provide a detailed account of observed variability between the expected and measured building response.…”
Section: Introductionsupporting
confidence: 82%
“…To ensure fair compensation for participation of intelligent building energy systems in the service markets, it is of critical importance to accurately forecast energy consumption baseline associated with nominal operation. This is consistent with current paradigms for grid operation and market designs, as well as proposed market designs for aggregated demand side flexibility as presented in [6]. In [7] the authors provide a detailed account of observed variability between the expected and measured building response.…”
Section: Introductionsupporting
confidence: 82%
“…1. The attributes of an electric flexibility service (except for the attribute location) [36]. [38,40], since changing their power consumption would have serious impact on their luminous capability.…”
Section: Consuming Der: Residential Loadsmentioning
confidence: 99%
“…Many energy systems are abstracted as idealized energy buffers subjected to power and energy constraints (1) and (2) only, see [6], [18], among others. Such systems are referred to as PE-systems, and their feasible sets are called PE-polytopes.…”
Section: ) State Constraintsmentioning
confidence: 99%
“…The importance of aggregation as a key enabler for incorporating large numbers of flexible systems has been highlighted in numerous works, e.g. , [2]- [6]. The tasks of collecting, aggregating and controlling the flexibility of a group of systems are performed by an entity called aggregator [7], [8].…”
Section: Introductionmentioning
confidence: 99%